The impact of long COVID on physical and cardiorespiratory parameters: A systematic review - Imane Salmam; Marc-Olivier Dubé; Imane Zahouani; Alexis Ramos; François Desmeules; Krista L. Best; Jean-Sébastien Roy (PLoS ONE, 2025)
Background Since the emergence of COVID-19, millions worldwide have continued to experience persistent symptoms months after infection. Among these, physical and cardiorespiratory impairments are frequently reported, but remain poorly understood. This systematic review aimed to identify and synthesize evidence regarding physical and cardiorespiratory impairments in individuals with long COVID, defined as symptoms persisting for at least three months post-infection. Methods and findings A structured search was conducted across the MEDLINE, Embase, CINAHL, and Web of Science databases to identify cross-sectional and longitudinal cohort studies on physical and cardiorespiratory deficits in adults with long COVID. Twenty-two studies involving 3,041 adults with long COVID were included. Critical appraisal using the JBI-APT indicated that most studies had clear inclusion criteria (17/22), well-defined study populations (17/22), and valid exposure measurements (16/22), though confounding factors were often unaddressed (9/22 unclear or not reported). Findings indicate that while adults with long COVID displayed normal pulmonary function at rest, including Forced Vital Capacity (FVC), Forced Expiratory Volume (FEV 1 ), Total Lung Capacity (TLC), and resting Arterial oxygen saturation (SpO 2 ) , significant impairments in exercise capacity were identified. Notably, all studies assessing the 6-minute walk test (6MWT) reported reduced distances, consistently falling below the 50 th percentile of normative values. Additionally, VO₂ peak was decreased in most studies (7/10), falling below 80% of the predicted value, indicating impaired aerobic capacity. Lower Diffusing Capacity of the Lungs for Carbon Monoxide (DLCO) values were observed in three out of six studies, with values below 75% of predicted, suggesting impaired gas exchange efficiency during exertion. Conclusion Despite preserved resting lung function, these findings highlight significant physical deconditioning in Long COVID adults, with substantial reduction in exercise capacity. Routine assessments should include more sensitive measures, such as the 6MWT and VO₂peak, to detect subtle exercise limitations, even in patients with normal resting SpO₂, to better inform rehabilitation interventions.